2019
DOI: 10.3390/agronomy9040170
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Year N and P Removal of a 10-Year-Old Surface Flow Constructed Wetland Treating Agricultural Drainage Waters

Abstract: Surface flow constructed wetlands (SFCWs) can be effectively used to treat agricultural drainage waters, reducing N and P surface water pollution. In the Venice Lagoon drainage basin (northeastern Italy), an SFCW was monitored during 2007-2013 to assess its performance in reducing water, N, and P loads more than 10 years after its creation. Nitrogen concentrations showed peaks during winter due to intense leaching from surrounding fields. Phosphorus concentrations were higher after prolonged periods with no di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…It was reported that SFCWs can be an inexpensive and efficient nature-based solution for the reduction of non-point source pollution, especially for nitrogen and phosphorus (Tolomio et al 2019, Pugliese et al 2020, and they were used for that purpose in different countries (Song et al 2019). Nitrogen removal/retention in SFCWs mainly depends on the biological and physico-chemical mechanisms (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that SFCWs can be an inexpensive and efficient nature-based solution for the reduction of non-point source pollution, especially for nitrogen and phosphorus (Tolomio et al 2019, Pugliese et al 2020, and they were used for that purpose in different countries (Song et al 2019). Nitrogen removal/retention in SFCWs mainly depends on the biological and physico-chemical mechanisms (e.g.…”
Section: Introductionmentioning
confidence: 99%